MEDICS medical image communication system : a java implemented DICOM image viewer and communication system - Bobis, Daniel E.; Domingo, Lourdes E.; Laraya, Jennifer A. (2002)
The objectives and significance of the thesis project will be discussed further in Part I (Introduction) of the thesis paper. Why it is necessary to create a more efficient and practical means of diagnosis and analysis of diseases and ailments and why it is better to have a standardized system of medical imaging and communications are all explained in greater details. For part II, (Review of Related literature), the necessary background information for understanding what DICOM means, the DICOM parts and its brief history are discussed. The advantages of Java language over the other object-oriented and non-object-oriented languages are expounded. Few existing Java and non-Java implementations of the DICOM standard are discussed mentioned, their main functions are discussed and snapshots of these implementations are also included. The few DCMTK (DICOM Toolkit) functions that are used to validate the software project are discuss in details in this part. Part III (System Design) discussed about the software architecture of the MedICS system, the software specificaions and the implementation of data encapsulation. The in depth explanations of the major classes developed for the software are included in this part. Part IV (Discussion) discussed the justification of the technology used for the MedICS software and its features against existing implementations.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Medicine -- Communication systems; Diagnostic imaging -- Digital techniques; Digital imaging and communications in medicine (DICOM).; MEDICS (Computer program).